Thermoplastic resin composition

The thermoplastic resin composition, featuring crosslinked polyhydroxyalkanoate resin particles and a crystal nucleating agent, addresses the issue of impact resistance in molded bodies, achieving superior tensile impact strength and biodegradability.

JP2025063462APending Publication Date: 2025-04-16KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172681
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing thermoplastic resin compositions lack sufficient impact resistance in their molded bodies, limiting their practical applications.

Method used

A thermoplastic resin composition is developed, comprising 40-99 parts by weight of a thermoplastic resin (A), 1-60 parts by weight of crosslinked resin particles (B) with a polyhydroxyalkanoate resin and a gel fraction of 50% or more, and 0.05-20.00 parts by weight of a crystal nucleating agent (C).

Benefits of technology

The composition provides molded bodies with excellent impact resistance, as evidenced by enhanced tensile impact strength, while maintaining biodegradability due to the use of biodegradable polyhydroxyalkanoate resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063462000001
    Figure 2025063462000001
  • Figure 2025063462000002
    Figure 2025063462000002
  • Figure 2025063462000003
    Figure 2025063462000003
Patent Text Reader

Abstract

To provide a novel thermoplastic resin composition capable of producing a molded article with superior impact strength.SOLUTION: Provided is a thermoplastic resin composition comprising: a thermoplastic resin (A); crosslinked resin particles (B) containing a polyhydroxyalkanoate-based resin and having a gel fraction of 50% or more; and (C) a nucleating agent, each component being included in a specific amount.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition. [Background technology]

[0002] Plastic waste places a burden on the global environment, affecting ecosystems, emitting harmful gases when burned, and contributing to global warming through the large amount of heat generated by combustion. There has been active development of biodegradable plastics as a material that can solve these problems.

[0003] Patent Document 1 describes a biodegradable, environmentally friendly thermoplastic resin composition that is composed of 100 parts by weight of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) and 0.1 to 20 parts by weight of poly(3-hydroxyalkanoate) particles having an average particle size of 300 μm or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-161802 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the above-mentioned conventional techniques are not sufficient from the viewpoint of the impact resistance of articles molded from thermoplastic resin compositions, and there is room for further improvement.

[0006] One embodiment of the present invention has been made in consideration of the above-mentioned current situation, and an object of the present invention is to provide a novel thermoplastic resin composition that can provide a molded article having excellent impact resistance. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that a thermoplastic resin composition containing a polyhydroxyalkanoate resin and crosslinked resin particles satisfying a specific gel fraction can provide a molded article having excellent impact resistance, and have completed one embodiment of the present invention.

[0008] That is, one embodiment of the present invention includes the following configuration. [1] A thermoplastic resin composition comprising: 40 to 99 parts by weight of a thermoplastic resin (A); 1 to 60 parts by weight of crosslinked resin particles (B) containing a polyhydroxyalkanoate resin and having a gel fraction of 50% or more (wherein the total amount of the thermoplastic resin (A) and the crosslinked resin particles (B) is 100 parts by weight); and 0.05 to 20.00 parts by weight of a crystal nucleating agent (C). [2] The thermoplastic resin composition according to [1], wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin. [3] The thermoplastic resin composition according to [1] or [2], wherein the crosslinked resin particles (B) have a volume average particle size of 0.10 μm to 10.00 μm. [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the crosslinked resin particles (B) are crosslinked using a peroxide. [5] The thermoplastic resin composition according to [4], wherein the crosslinked resin particles (B) are crosslinked in the presence of the peroxide and a polyfunctional compound. [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the crosslinked resin particles (B) are not foamed. [7] The thermoplastic resin composition according to any one of [1] to [6], wherein the crystal nucleating agent (C) contains a sugar alcohol compound. [8] The thermoplastic resin composition according to any one of [1] to [6], wherein the crystal nucleating agent (C) contains pentaerythritol. [9] A molded article obtained by molding the thermoplastic resin composition according to any one of [1] to [8].

[10] The molded article according to [9], which is a film molded article, a sheet molded article, a blow molded article, an extrusion molded article, a vacuum molded article, or an injection molded article. Effect of the Invention

[0009] According to one embodiment of the present invention, it is possible to provide a novel thermoplastic resin composition that can provide a molded article having excellent impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0011] [1. Thermoplastic resin composition] A thermoplastic resin composition according to one embodiment of the present invention comprises 40 to 99 parts by weight of a thermoplastic resin (A), 1 to 60 parts by weight of crosslinked resin particles (B) containing a polyhydroxyalkanoate resin and having a gel fraction of 50% or more (wherein the total amount of the thermoplastic resin (A) and the crosslinked resin particles (B) is 100 parts by weight), and 0.05 to 20.00 parts by weight of a crystal nucleating agent (C).

[0012] In this specification, the "thermoplastic resin composition according to one embodiment of the present invention" may be referred to as the "resin composition of the present invention." The crosslinked resin particles (B) contained in the resin composition of the present invention may also be referred to as the crosslinked resin particles of one embodiment of the present invention. In this specification, the "crosslinked resin particles (B) according to one embodiment of the present invention" may be referred to as the "crosslinked resin particles (B) of the present invention."

[0013] The present resin composition has an advantage that it can provide a molded article having excellent impact resistance. In this specification, the impact resistance of a molded article is defined as "tensile impact strength (kJ / m 2 The strength of the material can be evaluated by its tensile impact strength (kJ / m 2 The method for measuring the above will be described in detail in the Examples below.

[0014] The polyhydroxyalkanoate-based resin contained in the present crosslinked resin particles (B) is a biodegradable resin. Therefore, the present crosslinked resin particles (B) can be biodegradable. The present resin composition contains the crosslinked resin particles (B) that can be biodegradable, and is therefore advantageous in terms of biodegradability.

[0015] First, the crosslinked resin particles (B) will be described.

[0016] <Crosslinked resin particles (B)> The crosslinked resin particles (B), i.e., the present crosslinked resin particles (B), contain a polyhydroxyalkanoate resin and have a gel fraction of 50% or more. In this specification, the "polyhydroxyalkanoate resin" may be referred to as "PHA". The present resin composition contains the present crosslinked resin particles (B), and thus can provide a molded article having excellent impact resistance. In other words, the present crosslinked resin particles (B) can be used as a modifier or impact resistance improver for thermoplastic resins.

[0017] (PHAs) As described above, the polyhydroxyalkanoate resin is biodegradable and is a type of aliphatic polyester.

[0018] "PHA" is a general term for polymers containing hydroxyalkanoic acid as a monomer unit (monomer repeating unit), and is generally biodegradable. PHA is an aliphatic polyester, preferably a polyester not containing an aromatic ring. In this specification, "PHA" refers to a polymer containing hydroxyalkanoic acid repeating units in an amount of 50 mol% or more of all monomer repeating units (100 mol%). PHA preferably contains hydroxyalkanoic acid repeating units in an amount of 60 mol% or more, more preferably 70 mol% or more, of all monomer repeating units (100 mol%).

[0019] There is no particular limitation on the PHA. Examples of PHA include polyglycolic acid, poly(3-hydroxyalkanoate)-based resin (hereinafter sometimes referred to as "P3HA"), poly(4-hydroxyalkanoate)-based resin, and the like. As the PHA, only one type may be used alone, or two or more types may be used in combination. The PHA preferably contains a poly(3-hydroxyalkanoate)-based resin, and more preferably is a poly(3-hydroxyalkanoate)-based resin (in other words, composed only of a poly(3-hydroxyalkanoate)-based resin).

[0020] In this specification, "polyglycolic acid" refers to a resin containing 50 mol % or more of repeating units represented by [-CH2-CO-O-] out of all monomer repeating units (100 mol %). Polyglycolic acid may contain 60 mol % or more, 70 mol % or more, 80 mol % or more, or 90 mol % or more of repeating units represented by [-CH2-CO-O-] out of all monomer repeating units (100 mol %).

[0021] The polyglycolic acid may be a homopolymer of glycolic acid, or a copolymer of glycolic acid and a monomer other than glycolic acid (for example, a copolymer of glycolic acid and lactic acid, a copolymer of glycolic acid and caprolactone, etc.).

[0022] Polyglycolic acid can be obtained by known methods such as condensation polymerization of glycolic acid and ring-opening polymerization of glycolide.

[0023] The P3HA is a 3-hydroxyalkanoic acid repeating unit represented by the formula: [-CHR-CH2-CO-O-] (wherein R is C n H 2n+1 where n is an integer of 1 or more and 15 or less.) is a polyhydroxyalkanoate containing the 3-hydroxyalkanoic acid repeating unit as an essential repeating unit. In this specification, "P3HA" refers to a resin containing 50 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %). The P3HA preferably contains 60 mol % or more, and more preferably 70 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %).

[0024] P3HA is not particularly limited, and may be a homopolymer containing the repeating unit described above, or a copolymer containing the repeating unit described above. Examples of the copolymer include copolymers of 3-hydroxybutanoic acid (hereinafter sometimes referred to as "3HB") and one or more monomers selected from the group consisting of 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, and 3-hydroxyoctadecanoic acid. Alternatively, another example of the copolymer may be, for example, a copolymer of 3HB and one or more monomers selected from the group consisting of 4-hydroxybutanoic acid, 4-hydroxypentanoic acid, 4-hydroxyhexanoic acid, 4-hydroxyheptanoic acid, 4-hydroxyoctanoic acid, 4-hydroxynonanoic acid, 4-hydroxydecanoic acid, 4-hydroxyundecanoic acid, 4-hydroxydodecanoic acid, 4-hydroxytridecanoic acid, 4-hydroxytetradecanoic acid, 4-hydroxyhexadecanoic acid, and 4-hydroxyoctadecanoic acid.

[0025] Examples of P3HA include poly(3-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB"), which is a homopolymer of 3HB, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter, sometimes referred to as "P3HB3HH"), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB4HB"). Only one type of P3HA may be used, or two or more types may be used in combination. In this specification, "poly(X-co-Y)" refers to a copolymer containing X repeating units and Y repeating units, and is intended to mean a copolymer obtained by copolymerizing a monomer from which the X repeating units are derived and a monomer from which the Y repeating units are derived. In addition, during the production of P3HA by a microorganism, a small amount (about 1 mol% or less) of a monomer may be copolymerized, but if it does not significantly affect the physical properties of the obtained P3HA, the monomer is considered to be not copolymerized, and the product is called by a name that does not include the monomer.

[0026] P3HA can be produced by microorganisms. Such microbially produced P3HA is usually P3HA composed only of D-form (R-form) 3-hydroxyalkanoic acid repeating units. Among the microbially produced P3HA, P3HB, P3HB3HH and P3HB4HB are preferred, and P3HB3HH and P3HB4HB are more preferred, because they are easy to produce industrially.

[0027] It is also preferred that P3HA contains a 3-hydroxybutanoic acid (3HB) repeating unit. When P3HA contains a 3HB repeating unit, the composition ratio of the 3HB repeating unit in the total monomer repeating units (100 mol%) is preferably 60 mol% to 99 mol%, more preferably 61 mol% to 97 mol%, and even more preferably 62 mol% to 95 mol%, from the viewpoint of the balance between flexibility and strength. When the composition ratio of the 3HB repeating unit in P3HA is 60 mol% or more, there is an advantage that the rigidity of the crosslinked resin particle (B) can be further improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, there is an advantage that the flexibility of the crosslinked resin particle (B) tends to be further improved. The monomer composition ratio of P3HA can be measured by gas chromatography or the like (for example, see International Publication No. 2014 / 020838). As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0028] Microorganisms that produce P3HA are not particularly limited as long as they have the ability to produce P3HA. For example, the first P3HB-producing bacterium was Bacillus megaterium, discovered in 1925, and other natural microorganisms such as Cupriavidus necator (formerly classified as Alcaligenes eutrophus and Ralstonia eutropha) and Alcaligenes latus are also known. In these microorganisms, P3HB accumulates within the bacterial cells.

[0029] Also, as producers of copolymers of 3HB and other hydroxyalkanoic acids, Aeromonas caviae, which produces P3HB3HH, and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate), are known. In particular, in order to increase the productivity of P3HB3HH, Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, p4821-4830 (1997)) into which genes of P3HA synthase group have been introduced is preferred. Microorganisms that have been cultured under appropriate conditions to accumulate P3HA in the cells are used. In addition to the above, genetically modified microorganisms into which various P3HA synthesis-related genes have been introduced may be used depending on the P3HA to be produced, and culture conditions, including the type of substrate, may be optimized.

[0030] The weight average molecular weight of the PHA is not particularly limited. The weight average molecular weight of the PHA is preferably 50,000 to 3,000,000, preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the crosslinked resin particles (B) to have a low strength can be reduced or avoided. Also, when the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the low molecular weight component to be sticky can be reduced or avoided. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less can have an advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention. The numerical value of the weight average molecular weight of the PHA is a value obtained by measuring the PHA before the crosslinking treatment.

[0031] The weight average molecular weight can be measured by using gel permeation chromatography (GPC) (Shimadzu Corporation's "High Performance Liquid Chromatograph 20A System"), polystyrene gel (Showa Denko KK's "KG 4A", "K-806M", etc.) as a column, and chloroform as a mobile phase. The weight average molecular weight can be determined as a molecular weight converted into polystyrene using a calibration curve obtained by measuring polystyrene with a known molecular weight by the same measurement method. In this case, the calibration curve can be created using polystyrene with weight average molecular weights of 31,400, 197,000, 668,000, and 1,920,000. As the column for the GPC, a column appropriate for measuring the molecular weight may be used.

[0032] (Gel fraction) In this specification, the term "crosslinked resin particles" refers to a resin particle having a crosslinked structure in which the molecular chains of the resin constituting the resin particle are bonded intramolecularly and / or intermolecularly. That is, the present crosslinked resin particles (B) may have a crosslinked structure in which the molecular chains of PHA are bonded together. The amount of crosslinked structures in the crosslinked resin particles (B) affects the gel fraction of the crosslinked resin particles (B), and specifically, the more crosslinked structures there are, the higher the gel fraction. The present crosslinked resin particles (B) have a certain amount or more of crosslinked structures, and therefore exhibit a high gel fraction, specifically, a gel fraction of 50% or more. Since the present crosslinked resin particles (B) have a gel fraction of 50% or more, the crosslinked resin particles (B) have excellent hardness, heat resistance, and solvent resistance.

[0033] The value of the gel fraction is preferably 60% or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. It may also be 85% or more, or 90% or more. The upper limit of the gel fraction is not particularly limited, and may be 100% or less. From the viewpoint of production efficiency of the crosslinked resin particles (B), the upper limit of the gel fraction is preferably 99.5% or less, more preferably 99% or less. The upper limit of the gel fraction may also be 98% or less, 97% or less, or 96% or less.

[0034] The gel fraction is a value measured as follows: (1) A dried product of crosslinked resin particles is added to chloroform so that the concentration becomes 0.7% by weight, and the resulting mixture is kept at 60°C for 30 minutes to obtain a chloroform solution; (2) After that, the chloroform solution is allowed to stand at room temperature for 3 hours, and then the chloroform solution is filtered through a membrane filter having a pore size of 0.45 μm; (3) The gel remaining on the filter is dried, and the weight of the dried gel together with the filter is measured, and the gel fraction is calculated using the following formula. Formula: gel fraction (%)={(weight of filter including dried gel−weight of filter only) / weight of dried crosslinked resin particles used in measurement}×100.

[0035] (Volume average particle size) The crosslinked resin particles (B) preferably have a volume average particle diameter of 0.10 μm to 10.00 μm. This configuration allows the crosslinked resin particles (B) to be suitably used in various applications as described below. From the viewpoint of practical use, the lower limit of the volume average particle diameter is more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, from the viewpoint of productivity (production of PHA and / or crosslinking treatment, etc.), the upper limit of the volume average particle diameter is more preferably 8.00 μm or less, and even more preferably 5.00 μm or less.

[0036] In this specification, the volume average particle diameter (MV) of the crosslinked resin particles is a value obtained by measuring an aqueous dispersion liquid in which the crosslinked resin particles are dispersed in an aqueous medium. More specifically, the volume average particle diameter (MV) of the crosslinked resin particles is a value calculated by the following formula (1), i.e., formula (2), when the particle diameters of the individual crosslinked resin particles contained in a group of k total crosslinked resin particles are d1, d2,...di...dk in ascending order, and the volumes of the individual crosslinked resin particles are V1, V2,...Vi...Vk (here, the volume of the crosslinked resin particles with particle diameter di is Vi).

[0037]

number

[0038] In addition, a general-purpose measuring device can be used as a device for measuring the particle size and volume of the crosslinked resin particles in the aqueous dispersion, and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. In addition, in this specification, the volume average particle size of the uncrosslinked resin particles can be measured by replacing "crosslinked resin particles" with "uncrosslinked resin particles" in the above method.

[0039] (Peroxide) The crosslinked structure in the present crosslinked resin particle (B) is not particularly limited, but is preferably crosslinked using a peroxide. That is, the present crosslinked resin particle (B) is preferably crosslinked using a peroxide. When a peroxide is used, radicals generated by decomposition of the peroxide act on the molecules of the resin (e.g., PHA) constituting the resin particle. As a result, the molecular chains of the resin constituting the resin particle are directly bonded to each other, and a crosslinked structure can be formed.

[0040] When the crosslinked resin particles (B) are crosslinked using a peroxide, the aqueous dispersion containing the crosslinked resin particles (B) may contain substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide). Alternatively, when the crosslinked resin particles (B) are crosslinked using a peroxide, substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide) may adhere to the surface of the obtained crosslinked resin particles (B). That is, when the present crosslinked resin particles (B) are crosslinked using a peroxide, the present crosslinked resin particles (B) or the present resin composition may contain substances derived from the peroxide (such as decomposition products of the peroxide and unreacted peroxide). When the present crosslinked resin particles (B) or the present resin composition contain substances derived from the peroxide, it is found that the crosslinked resin particles (B) are crosslinked using a peroxide by analyzing the crosslinked resin particles (B) or the present resin composition.

[0041] The peroxide may be an organic peroxide or an inorganic peroxide. The peroxide is preferably an organic peroxide because it can increase the gel fraction more efficiently.

[0042] As the organic peroxide, it is preferable to use at least one selected from the group consisting of diacyl peroxides, alkyl peroxy esters, dialkyl peroxides, hydroperoxides, peroxy ketals, peroxy carbonates, and peroxy dicarbonates, taking into consideration the heating temperature and / or time during the crosslinking treatment.

[0043] Specific examples of such organic peroxides include butyl peroxy neododecanoate, octanoyl peroxide, dilauroyl peroxide, succinic peroxide, a mixture of toluoyl peroxide and benzoyl peroxide, benzoyl peroxide, bis(butylperoxy)trimethylcyclohexane, butylperoxylaurate, dimethyldi(benzoylperoxy)hexane, bis(butylperoxy)methylcyclohexane, bis(butylperoxy)cyclohexane, and butylperoxybenzo. ester, butyl bis(butylperoxy)valerate, dicumyl peroxide, di-t-hexyl peroxide, t-butylperoxy 2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxymethyl monocarbonate, t-pentylperoxymethyl monocarbonate, t-hexylperoxymethyl monocarbonate, t-heptylperoxymethyl monocarbonate, t-octylperoxymethyl monocarbonate, 1 ,1,3,3-tetramethylbutylperoxymethyl monocarbonate, t-butylperoxyethyl monocarbonate, t-pentylperoxyethyl monocarbonate, t-hexylperoxyethyl monocarbonate, t-heptylperoxyethyl monocarbonate, t-octylperoxyethyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyethyl monocarbonate, t-butylperoxy n-propyl monocarbonate, t-pentylperoxy n-propyl monocarbonate, t-hexylperoxyethyl monocarbonate peroxy n-propyl monocarbonate, t-heptyl peroxy n-propyl monocarbonate, t-octyl peroxy n-propyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxy n-propyl monocarbonate, t-butyl peroxy isopropyl monocarbonate, t-pentyl peroxy isopropyl monocarbonate, t-hexyl peroxy isopropyl monocarbonate, t-heptyl peroxy isopropyl monocarbonate, t-octyl peroxy isopropyl monocarbonate, 1,1,3,3-Tetramethylbutylperoxyisopropyl monocarbonate, t-butylperoxyn-butyl monocarbonate, t-pentylperoxyn-butyl monocarbonate, t-hexylperoxyn-butyl monocarbonate, t-heptylperoxyn-butyl monocarbonate, t-octylperoxyn-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyn-butyl monocarbonate, t-butylperoxyisobutyl monocarbonate, t-pentylperoxyisobutyl monocarbonate, t -Hexylperoxyisobutylmonocarbonate, t-heptylperoxyisobutylmonocarbonate, t-octylperoxyisobutylmonocarbonate, 1,1,3,3-tetramethylbutylperoxyisobutylmonocarbonate, t-butylperoxysec-butylmonocarbonate, t-pentylperoxysec-butylmonocarbonate, t-hexylperoxysec-butylmonocarbonate, t-heptylperoxysec-butylmonocarbonate, t-octylperoxysec-butylmonocarbonate peroxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy sec-butyl monocarbonate, t-butylperoxy t-butyl monocarbonate, t-pentylperoxy t-butyl monocarbonate, t-hexylperoxy t-butyl monocarbonate, t-heptylperoxy t-butyl monocarbonate, t-octylperoxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy t-butyl monocarbonate, t-butylperoxy 2-ethylhexyl monocarbonate, t-pentylperoxy 2-ethylhexyl monocarbonate, ethylhexyl monocarbonate, t-hexylperoxy 2-ethylhexyl monocarbonate, t-heptylperoxy 2-ethylhexyl monocarbonate, t-octylperoxy 2-ethylhexyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexyl monocarbonate, diisobutyl peroxide, cumylperoxy neodecanoate, di-n-propylperoxydicarbonate, diisopropylperoxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, bis(2-ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-hexylperoxypivalate, t-butylperoxypivalate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, disuccinic acid peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy) Examples of organic peroxides include hexane, t-hexylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoylperoxide, t-butylperoxy-2-ethylhexylcarbonate, t-butylperoxyisopropylcarbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, t-butylperoxybenzoate, t-amylperoxy, 3,5,5-trimethylhexanoate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, and 2,2-di-t-butylperoxybutane. The organic peroxides may be used alone or in combination of two or more.

[0044] Among these, t-butylperoxyisopropyl monocarbonate, t-pentylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-pentylperoxy2-ethylhexyl monocarbonate, t-hexylperoxy2-ethylhexyl monocarbonate, t-amylperoxyisopropyl monocarbonate, di-t-hexyl peroxide, t-butylperoxy2-ethylhexanoate, Preferred organic peroxides are t-butyl peroxyisobutyrate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate, because they can efficiently promote crosslinking of the resin that constitutes the resin particles.

[0045] Since the heating temperature during crosslinking treatment can be set low, the peroxide is preferably a compound exhibiting a one-hour half-life temperature of 200° C. or less, more preferably a compound exhibiting a one-hour half-life temperature of 170° C. or less, and even more preferably a compound exhibiting a one-hour half-life temperature of 140° C. or less. The lower limit of the one-hour half-life temperature of the peroxide may be 50° C. or more, 60° C. or more, or 70° C. or more.

[0046] Particularly preferred organic peroxides exhibiting such a one-hour half-life temperature are t-butylperoxyisopropylmonocarbonate, t-butylperoxy2-ethylhexylmonocarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate.

[0047] The case where the peroxide is an inorganic peroxide will be described. Examples of the inorganic peroxide include hydrogen peroxide, potassium peroxide, calcium peroxide, sodium peroxide, magnesium peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate, taking into consideration the heating temperature and / or time during crosslinking treatment. Among them, hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred in terms of ease of handling and having a decomposition temperature suitable for the heating temperature during crosslinking treatment. The inorganic peroxide may be used alone or in combination of two or more. An organic peroxide and an inorganic peroxide may be used in combination.

[0048] (polyfunctional compound) The crosslinked structure in the present crosslinked resin particle (B) may be introduced by using only peroxide, but it is preferable that it is introduced by using both peroxide and polyfunctional compound. That is, it is preferable that the present crosslinked resin particle (B) is crosslinked in the presence of peroxide and polyfunctional compound. When both peroxide and polyfunctional compound are used, it is possible to increase the gel fraction of the crosslinked resin particle (B) with a smaller amount of peroxide compared to the case where only peroxide is used.

[0049] The polyfunctional compound refers to a compound having two or more functional groups (e.g., radical reactive groups) in one molecule that can crosslink the resin (e.g., PHA) that constitutes the resin particles. The polyfunctional compound is not particularly limited, but is preferably a compound that is reactive with a radical generated from a peroxide, and is particularly preferably a compound having two or more radical reactive groups in one molecule. The radical reactive group is preferably at least one selected from the group consisting of a vinyl group, an allyl group, an acryloyl group, and a methacryloyl group.

[0050] Such polyfunctional compounds are not particularly limited, but examples thereof include allyl (meth)acrylate, allyl alkyl (meth)acrylates, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferably, the compound is one or more selected from the group consisting of allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and more preferably, the compound is one or more selected from the group consisting of allyl methacrylate and triallyl isocyanurate.

[0051] When a crosslinked structure is formed in the presence of a polyfunctional compound, the resulting crosslinked resin particles (B) may usually contain a structure derived from the polyfunctional compound, in which case the molecular chains of the resin constituting the resin particles are bonded to each other via the structure derived from the polyfunctional compound.

[0052] (Other Ingredients) The present crosslinked resin particles (B) are crosslinked resin particles (B) containing PHA. Therefore, the present crosslinked resin particles (B) may be crosslinked resin particles (B) containing only PHA, or may be crosslinked resin particles (B) containing other components other than PHA. Examples of the other components include resins other than PHA, antioxidants, hydrolysis inhibitors, antiblocking agents, crystal nucleating agents, lubricants, and ultraviolet absorbers.

[0053] The ratio of PHA in the present crosslinked resin particle (B) is not particularly limited. The content of PHA in 100% by weight of the resin component of the present crosslinked resin particle (B) may be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and may be 99% by weight or more. The upper limit of the content of PHA in 100% by weight of the resin component of the present crosslinked resin particle (B) is not particularly limited, and may be 100% by weight or less. Note that the "resin component of the crosslinked resin particle" refers to the resin that essentially constitutes the crosslinked resin particle, and does not include the component that crosslinks the molecular chains of the resin (e.g., a structure derived from a polyfunctional compound) and the residue of the component used for crosslinking the molecular chains of the resin (e.g., unreacted peroxide, decomposition product of peroxide, unreacted polyfunctional compound, etc.).

[0054] Examples of the resin other than PHA include aliphatic polyesters other than PHA and aliphatic aromatic polyesters. Examples of the aliphatic polyesters other than PHA include (i) polycaprolactone (PCL), (ii) polylactic acid (PLA), and (iii) aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed. Specific examples of the aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed include polyethylene succinate, polybutylene succinate (hereinafter sometimes referred to as "PBS"), polyhexamethylene succinate, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polybutylene succinate adipate (hereinafter sometimes referred to as "PBSA"), polyethylene sebacate, polybutylene sebacate, etc. The aliphatic aromatic polyester includes an aliphatic aromatic polyester (both an aliphatic compound and an aromatic compound are used as monomers) obtained by copolymerizing the monomers using both an aliphatic compound and an aromatic compound. Examples of the aliphatic aromatic polyester include polybutylene adipate terephthalate (hereinafter sometimes referred to as "PBAT"), polybutylene sebacate terephthalate (hereinafter sometimes referred to as "PBSeT"), polybutylene azelate terephthalate (hereinafter sometimes referred to as "PBAzT"), polybutylene succinate terephthalate (hereinafter sometimes referred to as "PBST"), and polybutylene succinate adipate terephthalate (hereinafter sometimes referred to as "PBSAT"). These resins other than PHA may be used alone or in combination of two or more. In the present crosslinked resin particles (B), the resins other than PHA may be crosslinked or not crosslinked.

[0055] The present crosslinked resin particles (B) are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. In other words, the present crosslinked resin particles (B) preferably do not substantially contain air bubbles inside the particles. "Substantially does not contain air bubbles inside the particles" means that the volume of air bubbles (spaces) is 10% or less in 100% volume of the crosslinked resin particles (B).

[0056] When the crosslinked resin particles (B) are not expanded, the apparent density of the crosslinked resin particles (B) is relatively large. The apparent density of the crosslinked resin particles (B) is 0.6 g / cm. 3 It is preferable that the density exceeds 0.7 g / cm 3 More preferably, it is 0.9 g / cm or more. 3 The apparent density of the crosslinked resin particles (B) can be determined by the method described in JIS K0061 (Method for measuring density and specific gravity of chemical products) or JIS Z8807 (Method for measuring density and specific gravity of solids).

[0057] The average weight of each of the present crosslinked resin particles (B) is not particularly limited. For example, when the volume average particle size of the present crosslinked resin particles (B) is 10.00 μm or less, the average weight of each of the present crosslinked resin particles (B) can be much less than 0.1 mg.

[0058] The crosslinked resin particles (B) may be dried. The shape of the dried particles may be powder, pellets, crumbs, a film, a sheet, or the like, depending on the drying method.

[0059] (Method for producing crosslinked resin particles (B)) An example of a method for producing the present crosslinked resin particles (B) will be specifically described below. The present crosslinked resin particles (B) can be produced by crosslinking the molecular chains of the resin in an aqueous dispersion containing resin particles before crosslinking treatment in the presence of a peroxide. The term "resin particles" refers to particles composed of a resin component that essentially constitutes the crosslinked resin particles (B). When the resin component is composed only of PHA, the resin particles can also be called PHA particles. In order to efficiently crosslink the molecular chains of the resin, it is preferable to heat the aqueous dispersion of the resin particles containing the peroxide to a temperature suitable for decomposing the peroxide.

[0060] More specifically, the method for producing the crosslinked resin particles (B) preferably includes the steps of: (1) preparing an aqueous dispersion of resin particles in which pre-crosslinked resin particles (e.g., PHA particles) are dispersed in water; (2) adding a peroxide to the aqueous dispersion of resin particles to impregnate the resin particles with the peroxide; and (3) heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink the resin molecular chains (e.g., PHA molecular chains). More preferably, the method further includes the step of maintaining the heating temperature after all the peroxide has been added.

[0061] In step (1), for example, the aqueous dispersion of PHA particles may be an aqueous dispersion obtained by culturing a PHA-producing microorganism to accumulate PHA in the cells, and then disrupting the cells in the culture medium to separate and remove the cell components, or an aqueous dispersion obtained by concentrating or diluting the aqueous dispersion. According to such a method, the process from producing PHA particles by culturing a PHA-producing microorganism to crosslinking treatment can be carried out without separating the PHA particles from water.

[0062] Alternatively, an aqueous dispersion of resin particles (eg, PHA particles) can be prepared by dispersing dried resin particles (eg, PHA particles) in water.

[0063] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.

[0064] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.

[0065] The water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.

[0066] In the aqueous dispersion, the volume average particle diameter of the resin particles is preferably within the same range as the volume average particle diameter of the above-mentioned crosslinked resin particles (B). In the case of PHA particles produced by a PHA-producing microorganism, the volume average particle diameter can usually be within the above range, so that an aqueous dispersion of PHA particles having a desired volume average particle diameter can be obtained without carrying out a special process for adjusting the particle diameter.

[0067] The concentration of the resin particles in the aqueous dispersion is not particularly limited and can be set appropriately, but may be, for example, about 1 to 70% by weight, and preferably about 5 to 50% by weight.

[0068] The aqueous dispersion of resin particles preferably contains a dispersant in order to increase the dispersibility of the resin particles and to uniformly proceed with the crosslinking reaction. Examples of dispersants include anionic surfactants such as dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium lauryl sulfate, and sodium oleate; cationic surfactants such as lauryl trimethyl ammonium chloride; nonionic surfactants such as glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, and polyoxyethylene polyoxypropylene glycol; and water-soluble polymers such as polyvinyl alcohol, ethylene-modified polyvinyl alcohol, polyvinylpyrrolidone, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polymethacrylic acid, and sodium polymethacrylate. Only one of these dispersants may be used, or two or more of them may be used in combination.

[0069] When a dispersant is used, the content (addition amount) of the dispersant in the aqueous dispersion is not particularly limited. The content of the dispersant in the aqueous dispersion may be, for example, 0.1 to 10 parts by weight, preferably 0.5 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the resin particles.

[0070] In step (2), a peroxide is added to the aqueous dispersion of resin particles obtained in step (1) to impregnate the resin particles with the peroxide. The peroxide may be any of those mentioned above. Peroxide may be added in various forms, such as solid or liquid. Alternatively, a liquid form diluted with a diluent may be added. The peroxide may be added all at once, or may be added continuously or in portions.

[0071] When the peroxide and the polyfunctional compound are used in combination, it is preferable to add the polyfunctional compound to the aqueous dispersion of the resin particles in step (2). The polyfunctional compound can be any of those mentioned above. The polyfunctional compound can be added in various forms, such as solid or liquid. A liquid diluted with a diluent or the like may also be added. The polyfunctional compound may be added all at once, continuously, or in portions.

[0072] In step (2), the method of impregnating the resin particles with the peroxide and any polyfunctional compound may be such that, after or while adding these compounds to the aqueous dispersion of the resin particles, the temperature of the aqueous dispersion is set to, for example, 0°C or higher but lower than a temperature suitable for decomposing the peroxide employed in the next step (3), and the temperature is maintained, for example, for about 1 minute to 5 hours while stirring the aqueous dispersion. Specifically, the temperature of the aqueous dispersion during impregnation may be about 0°C to 80°C.

[0073] The amount of the peroxide used can be appropriately set in consideration of the gel fraction of the crosslinked resin particles (B). The amount of the peroxide used is, for example, preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0074] According to the production method in which resin particles are crosslinked in an aqueous dispersion using a peroxide, crosslinking can be promoted while maintaining the particle size (volume) before crosslinking, and crosslinked resin particles (B) can be easily obtained. On the other hand, in the method in which the resin is crosslinked by melt kneading in the presence of a peroxide, it may be difficult to achieve this.

[0075] In addition, the production method in which resin particles are crosslinked in an aqueous dispersion using a peroxide has the advantage that it is easy to control the temperature increase caused by the heat generated during the crosslinking reaction, and crosslinked resin particles (B) having a safe and stable crosslinked structure (quality) can be efficiently obtained.

[0076] The amount of the polyfunctional compound used may be appropriately set in consideration of the gel fraction of the crosslinked resin particles (B). The amount of the polyfunctional compound used is, for example, preferably 0.01 to 20 parts by weight, more preferably 0.05 to 15 parts by weight, even more preferably 0.1 to 10 parts by weight, even more preferably 0.2 to 5 parts by weight, and particularly preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0077] In step (3), the aqueous dispersion of resin particles impregnated with the peroxide is heated to a temperature suitable for decomposing the peroxide. The heating temperature is preferably within a range of about 25°C above and below the one-hour half-life temperature of the peroxide (one-hour half-life temperature -25°C to one-hour half-life temperature +25°C). Specifically, the heating temperature is preferably 30°C to 140°C, more preferably 50°C to 135°C, and even more preferably 60°C to 130°C. According to this method, it is possible to crosslink the resin at a temperature lower than the melting temperature of the resin (e.g., PHA), so that deterioration of the resin due to heating during the crosslinking treatment can be avoided. The melting temperature of PHA is, for example, 50°C to 210°C.

[0078] In the subsequent step (4), it is preferable to maintain the heating temperature. This allows the crosslinking reaction using the peroxide to proceed sufficiently. The time for maintaining the heating temperature is not particularly limited, but is preferably 1 minute to 15 hours, and more preferably 1 hour to 10 hours.

[0079] After the crosslinking reaction is completed, the crosslinked resin particles (B) are separated from the aqueous dispersion, and water is removed from the separated crosslinked resin particles (B) to obtain dried crosslinked resin particles (B). The method for separating the crosslinked resin particles (B) from the aqueous dispersion is not particularly limited, and for example, filtration, centrifugation, heat drying, freeze drying, spray drying, etc. can be used. For example, spray drying can be used to obtain dried crosslinked resin particles (B) directly from the aqueous dispersion. In addition, the crosslinked resin particles (B) can be extruded alone after separation from the aqueous dispersion, and the crosslinked resin particles (B) can be obtained in the form of pellets while completely removing the remaining moisture. In addition, a coagulation step using a coagulant and / or pH adjustment can be performed.

[0080] The content of the crosslinked resin particles (B) in the present resin composition is 1 to 60 parts by weight in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). According to this configuration, the thermoplastic resin composition can provide a molded product having excellent impact resistance. The content of the crosslinked resin particles (B) in the present resin composition may be 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the crosslinked resin particles (B) in the present resin composition is preferably 55 parts by weight or less, more preferably 53 parts by weight or less, and even more preferably 50 parts by weight or less in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the crosslinked resin particles (B) in the present resin composition may be 45 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the combined total of the thermoplastic resin (A) and the crosslinked resin particles (B).

[0081] <Thermoplastic resin (A)> In the present resin composition, the thermoplastic resin (A) can be said to be a matrix resin. The thermoplastic resin (A) is not particularly limited as long as it is a resin that can be molded into a desired shape by melting it by heating and then cooling and solidifying it. Specific examples of the thermoplastic resin (A) include polyolefin resins such as polyethylene and polypropylene, acrylic resins such as polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, and polymethyl methacrylic acid, AS resins, polyamides, polyacetals, polycarbonates, modified polyphenylene ethers, polyester resins, and cyclic polyolefins. These thermoplastic resins (A) may be used alone or in combination of two or more. The thermoplastic resin (A) preferably has a gel fraction of less than 50%. The thermoplastic resin (A) is preferably not crosslinked.

[0082] As the thermoplastic resin (A), polyester-based resins are particularly preferred, such as aliphatic polyesters (e.g., PHA, PLA, PCL, and aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed, etc.) and aliphatic aromatic polyesters.

[0083] The specific aspects of the aliphatic polyester and the aliphatic aromatic polyester are the same as those described in the (PHA) and (Other Components) sections of the <Crosslinked Resin Particles (B)> section above, so the description therein is incorporated by reference and will not be repeated here.

[0084] Since the crosslinked resin particles (B) contain PHA having biodegradability, it is preferable that the thermoplastic resin (A) also contains a resin having biodegradability, i.e., a biodegradable resin. This configuration has the advantage that the biodegradability of the entire thermoplastic resin composition and the entire molded body of the thermoplastic resin composition can be increased. Therefore, when the thermoplastic resin (A) contains a biodegradable resin, it is expected to be useful as a thermoplastic resin composition that addresses the problem of plastic waste and is friendly to the global environment. In addition, when the thermoplastic resin (A) contains a biodegradable resin, the present resin composition and its molded body can suppress soil pollution due to disposal. This can contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns." Furthermore, when the biodegradable resin contained in the thermoplastic resin (A) has marine decomposition in addition to soil decomposition, the resin composition and molded body containing the present crosslinked resin particles (B) can suppress marine pollution in addition to suppressing soil pollution due to disposal.

[0085] Furthermore, when the crosslinked resin particles (B) contain a resin produced from a plant-derived raw material, from the viewpoint of resource circulation, it is preferable that the thermoplastic resin (A) also contains a resin produced from a plant-derived raw material, and it is more preferable that the thermoplastic resin (A) is composed only of a resin produced from a plant-derived raw material.

[0086] The case where the thermoplastic resin (A) contains a biodegradable resin will be described. The thermoplastic resin (A) preferably contains 10% by weight to 100% by weight of a biodegradable resin in 100% by weight of the thermoplastic resin (A). The thermoplastic resin (A) more preferably contains 30% by weight or more of a biodegradable resin in 100% by weight of the thermoplastic resin (A), more preferably contains 50% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 90% by weight or more. The thermoplastic resin (A) may be composed of only a biodegradable resin.

[0087] Since the thermoplastic resin composition and its molded article can enjoy the impact resistance improving effect of the crosslinked resin particles (B), the biodegradable resin in the thermoplastic resin (A) preferably contains a polyester resin, more preferably contains an aliphatic polyester, and particularly preferably contains PHA and / or polylactic acid. The PHA used as the thermoplastic resin (A) preferably has a gel fraction of less than 50%. The PHA used as the thermoplastic resin (A) preferably does not have a crosslinked structure.

[0088] The case where the thermoplastic resin (A) contains PHA and / or polylactic acid as a biodegradable resin will be described below. The thermoplastic resin (A) preferably contains 10% by weight to 100% by weight of PHA and polylactic acid in total, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more, based on 100% by weight of the thermoplastic resin (A).

[0089] The PHA that can be used as the thermoplastic resin (A) is not particularly limited, and examples thereof include polyglycolic acid, P3HA, poly(4-hydroxyalkanoate) resins, etc. As the PHA, only one type may be used, or two or more types may be used in combination. As the PHA used as the thermoplastic resin (A), P3HA is particularly preferred.

[0090] A case where the crosslinked resin particles (B) contain P3HA and the thermoplastic resin (A) contains P3HA will be described. The P3HA that can be used as the thermoplastic resin (A) is the same as the P3HA related to the crosslinked resin particles (B), and the above-mentioned various P3HAs can be used. The P3HA contained in the thermoplastic resin (A) may be a resin having the same composition as the P3HA contained in the crosslinked resin particles (B), or may be a resin having a different composition and / or physical properties. The P3HA contained in the thermoplastic resin (A) is preferably a resin having a different composition and / or physical properties from the P3HA contained in the crosslinked resin particles (B), and is more preferably a resin harder than the P3HA contained in the crosslinked resin particles (B).

[0091] The case where the P3HA used as the thermoplastic resin (A) contains a 3-hydroxybutanoic acid (3HB) repeating unit will be described. In this case, from the viewpoint of the balance between flexibility and strength, the composition ratio of the 3HB repeating unit in the total monomer repeating units of P3HA (100 mol%) is preferably 80 mol% to 99 mol%, more preferably 82 mol% to 97 mol%. When the composition ratio of the 3HB repeating unit in P3HA is 80 mol% or more, the rigidity of P3HA can be improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, the flexibility of P3HA tends to be improved. As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0092] The weight average molecular weight of the PHA used as the thermoplastic resin (A) is not particularly limited, but is preferably 50,000 to 3,000,000, more preferably 100,000 to 2,000,000, and even more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less may have the advantage that the PHA is easy to manufacture and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0093] Polylactic acid usable as the thermoplastic resin (A) may be any conventionally known polylactic acid. The polylactic acid may be crystalline polylactic acid, amorphous polylactic acid, or a mixture of crystalline polylactic acid and amorphous polylactic acid.

[0094] The polylactic acid may be a homopolymer of lactic acid, a copolymer of lactic acid and other monomers, or a blend of a homopolymer of lactic acid and a copolymer of lactic acid and other monomers.

[0095] Examples of the other monomers include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides.

[0096] The lactic acid raw material for producing polylactic acid is not particularly limited, and L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be suitably used.

[0097] The method for producing polylactic acid is not particularly limited, and known methods such as dehydration condensation polymerization and ring-opening polymerization can be used.

[0098] The weight average molecular weight of the polylactic acid used as the thermoplastic resin (A) is not particularly limited, but is preferably 50,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 400,000. When the weight average molecular weight of the polylactic acid is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, polylactic acid having a weight average molecular weight of 1,000,000 or less can have the advantage that the polylactic acid is easy to produce and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0099] Regarding the PHA used as the thermoplastic resin (A), other aspects than those described above are the same as those explained in the section on (PHA), so the explanation therefor is incorporated by reference and will not be repeated here.

[0100] The content of the thermoplastic resin (A) in the present resin composition is 40 to 99 parts by weight in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). According to this configuration, the thermoplastic resin composition can provide a molded product having excellent impact resistance. The content of the thermoplastic resin (A) in the present resin composition may be 40 to 95 parts by weight, 45 to 93 parts by weight, 47 to 90 parts by weight, 50 to 80 parts by weight, 50 to 85 parts by weight, 50 to 75 parts by weight, or 50 to 70 parts by weight in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the thermoplastic resin (A) in the present resin composition may be 55 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 88 parts by weight or more, or 90 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B).

[0101] <Nucleating Agent (C)> The thermoplastic resin composition contains a crystal nucleating agent (C). When the thermoplastic resin composition contains a crystal nucleating agent (C), crystallization during molding is promoted when the thermoplastic resin is a crystalline resin, and molding processability, productivity, etc. can be improved. Specifically, when the thermoplastic resin composition contains a crystal nucleating agent (C), the processability and processing speed in processing such as injection molding, film molding, sheet molding, blow molding, and fiber spinning using the thermoplastic resin composition can be improved. In addition, specifically, when the thermoplastic resin composition contains a crystal nucleating agent (C), the solidification property in molding processing such as injection molding and blow molding using the thermoplastic resin composition can be improved, and the processing speed can be improved.

[0102] When the present thermoplastic resin composition contains a crystal nucleating agent, it has an advantage that a thermoplastic resin composition and a molded article thereof having excellent heat resistance or mechanical properties can be obtained. Specifically, the present thermoplastic resin composition contains a crystal nucleating agent (C), so that the crystals of the thermoplastic resin (A) become fine. This has the advantage that the mechanical properties of the molded article of the thermoplastic resin composition become stable and are less likely to change over time.

[0103] The crystal nucleating agent is not particularly limited, and conventionally known ones can be used. The crystal nucleating agent can be, for example, inorganic substances such as talc, kaolinite, montmorillonite, mica, synthetic mica, clay, zeolite, silica, carbon black, graphite, boron nitride, zinc oxide, titanium oxide, tin oxide, calcium carbonate, magnesium carbonate, aluminum oxide, neodymium oxide, barium sulfate, sodium chloride, and metal phosphate; sugar alcohol compounds derived from natural products such as erythritol, pentaerythritol, galactitol, mannitol, and arabitol; polysaccharides such as chitin and chitosan; polyols such as aliphatic alcohols (polyols), polyvinyl alcohol, and polyethylene oxide; sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, and terephthalic acid salts. metal salts of organic carboxylic acids such as potassium phosphate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate;Carboxylic acid amides such as ethylene stearic acid amide, ethylene bislauric acid amide, palmitic acid amide, hydroxystearic acid amide, erucic acid amide, and trimesic acid tris(t-butylamide), lauric acid esters, palmitic acid esters, oleic acid esters, stearic acid esters, erucic acid esters, N-oleyl palmitic acid ester, N-oleyl oleic acid ester, N-oleyl stearate ester, N-stearyl oleic acid ester, N-stearyl stearate ester, N-stearyl erucic acid ester, methylene bisstearate ester, ethylene bislauric acid ester, ethylene biscapric acid ester, ethylene bisoleic acid ester, ethylene bisstearic acid ester, ethylene biserucic acid ester, ethylene Examples of the nucleating agent include carboxylic acid esters such as butylene bisisostearate, butylene bisstearate, and p-xylylene bisstearate; dicarboxylic acid derivatives such as dimethyl adipate, dibutyl adipate, diisodecyl adipate, and dibutyl sebacate; cyclic compounds having a functional group C=O and one or more functional groups selected from the group consisting of NH, S, and O in the molecule, such as indigo, quinacridone, and quinacridone magenta; sorbitol derivatives such as bisbenzylidene sorbitol and bis(p-methylbenzylidene) sorbitol; compounds containing a nitrogen-containing heteroaromatic nucleus such as pyridine, triazine, and imidazole; phosphoric acid ester compounds, bisamides of higher fatty acids, and metal salts of higher fatty acids; branched polylactic acid; and low molecular weight poly(3-hydroxybutyrate). These crystal nucleating agents may be used alone or in combination of two or more.

[0104] In the present resin composition, the crystalline state of the thermoplastic resin (A) can be appropriately controlled, and the crystallization promoting effect on the aliphatic polyester resin is particularly high. Therefore, the crystal nucleating agent (C) preferably contains a sugar alcohol compound (e.g., a sugar alcohol compound derived from a natural product), more preferably contains one or more selected from the group consisting of erythritol, pentaerythritol, galactitol, mannitol, and arabitol, and further preferably contains pentaerythritol. The crystal nucleating agent (C) may be composed only of a sugar alcohol compound (e.g., a sugar alcohol compound derived from a natural product), may be composed only of one or more selected from the group consisting of erythritol, pentaerythritol, galactitol, mannitol, and arabitol, or may be composed only of pentaerythritol. By using the above-mentioned crystal nucleating agent (C), the crystallization of the thermoplastic resin (A) may be promoted in some cases.

[0105] Also preferred is an embodiment in which the crystal nucleating agent contains a compound represented by the following general formula (1): NH2-CHR-COOH...General formula (1) In the formula, R represents hydrogen or a monovalent aliphatic hydrocarbon group.

[0106] The crystal nucleating agent may consist solely of the compound represented by formula (1).

[0107] Examples of the monovalent aliphatic hydrocarbon group in R include, but are not limited to, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, amyl, hexyl, octyl, decyl, dodecyl, and octadecyl; alkenyl groups such as vinyl, allyl, isopropenyl, 1-butenyl, 2-butenyl, and 2-pentenyl. The monovalent aliphatic hydrocarbon group in R is preferably a group having 1 to 6 carbon atoms, and more preferably a group having 1 to 3 carbon atoms (e.g., methyl, ethyl, propyl, and isopropyl). Optical isomers exist in compounds in which R is a monovalent aliphatic hydrocarbon group. For example, α-alanine in which R is a methyl group includes not only L-α-alanine but also D-α-alanine. Both L-α-alanine and D-α-alanine can be used. Among the compounds represented by the general formula (1), glycine in which R is hydrogen and alanine in which R is a methyl group are preferred, and glycine is particularly preferred. Glycine is known to have three types of crystals with different structures, i.e., crystal polymorphs, namely α, β, and γ. Among these, γ-type crystals, which are stable crystals of glycine at room temperature, are preferred because they are highly effective as a crystal nucleating agent and are easy to obtain. These γ-type crystals can be distinguished from other crystal types by showing a characteristic peak at 2θ=25.2° in powder X-ray analysis using Cu-Kα rays. The compound represented by the general formula (1) has the advantage that it is decomposed together with the resin when the thermoplastic resin composition is decomposed by microorganisms in soil, etc., and therefore does not cause problems such as environmental pollution.

[0108] The particle size (median size) of the crystal nucleating agent is preferably a certain size or less (for example, 500 μm or less) in the thermoplastic resin (A). This configuration can further enhance the effect as a crystal nucleating agent. The particle size (median size) of the crystal nucleating agent can be measured by directly observing the size with an optical microscope or an electron microscope.

[0109] For example, a method for reducing the particle size of the crystal nucleating agent in the thermoplastic resin (A) to a certain size or less can be, for example, pulverizing the crystal nucleating agent to reduce the particle size and then dispersing it in the thermoplastic resin (A). As a pulverizing method, in addition to pulverization in a mortar, a conventionally known method such as a collision plate type or powder collision type jet mill, a bead mill, or a hammer mill can be used. In addition, the crystal nucleating agent can be reduced in size to a certain size or less by the shear force during melt kneading.

[0110] The content of the crystal nucleating agent is not particularly limited as long as it can promote the crystallization of the thermoplastic resin. The content of the crystal nucleating agent is 0.02 parts by weight to 20.00 parts by weight, preferably 0.03 parts by weight to 15.00 parts by weight, more preferably 0.05 parts by weight to 12.00 parts by weight, more preferably 0.10 parts by weight to 10.00 parts by weight, even more preferably 0.50 parts by weight to 8.00 parts by weight, even more preferably 0.50 parts by weight to 5.00 parts by weight, and particularly preferably 0.50 parts by weight to 3.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the crystal nucleating agent is within the above range, the effect as a crystal nucleating agent can be obtained while suppressing the decrease in viscosity during molding and the physical properties of the molded body.

[0111] Among the compounds mentioned above as crystal nucleating agents, there are some that can exert effects other than those of a crystal nucleating agent (for example, lubricants, plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, antistatic agents, etc.). In this specification, even if each of the above-mentioned compounds exerts effects other than those of a crystal nucleating agent, it is regarded as a crystal nucleating agent, and its content is regarded as the content of a crystal nucleating agent.

[0112] <Lubricant> The resin composition may further contain a lubricant. When the thermoplastic resin composition contains a lubricant, the surface smoothness of the obtained molded article can be improved. The lubricant is not particularly limited. Examples of the lubricant include, but are not limited to, fatty acid metal salts such as magnesium stearate and calcium stearate; fatty acid amides such as behenic acid amide, stearic acid amide, erucic acid amide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide; polyethylene wax, oxidized polyester wax, glycerin mono fatty acid esters such as glycerin monostearate, glycerin monobehenate, and glycerin monolaurate; organic acid monoglycerides such as succinic acid saturated fatty acid monoglycerides; sorbitan fatty acid esters such as sorbitan behenate, sorbitan stearate, and sorbitan laurate; polyglycerin fatty acid esters such as diglycerin stearate, diglycerin laurate, tetraglycerin stearate, tetraglycerin laurate, decaglycerin stearate, and decaglycerin laurate; and higher alcohol fatty acid esters such as stearyl stearate. The lubricant may be used alone or in combination of two or more.

[0113] The content of the lubricant (when a plurality of lubricants are used, the total content thereof) is not particularly limited as long as it can impart lubricity to the molded body. The content of the lubricant is preferably 0.01 to 20.00 parts by weight, more preferably 0.05 to 10.00 parts by weight, even more preferably 0.10 to 10.00 parts by weight, even more preferably 0.20 to 5.00 parts by weight, and particularly preferably 0.30 to 4.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the lubricant is within the above range, it is possible to obtain the effect as a lubricant while avoiding the bleeding out of the lubricant onto the surface of the molded body.

[0114] <Other ingredients> The present resin composition may contain other components, such as plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents, to the extent that the functions of the resulting molded article are not impaired.

[0115] The plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers such as polypropylene glycol sebacate ester, aliphatic dibasic acid ester-based plasticizers such as di-1-butyl adipate, di-n-butyl sebacate, and di-2-ethylhexyl azelate, glycerin-based plasticizers such as glycerin diacetomonolaurate, glycerin diacetomonocaprylate, and glycerin diacetomonodecanoate, polycarboxylic acid ester-based plasticizers such as tri-2-ethylhexyl acetyl citrate and tributyl acetyl citrate, and polyamide-based plasticizers such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, and polytetramethylene glycol. Examples of the plasticizer include alkylene glycol-based plasticizers, phosphoric acid ester-based plasticizers such as diphenyl-2-ethylhexyl phosphate and diphenyloctyl phosphate, epoxy-based plasticizers such as epoxidized soybean oil and epoxidized linseed oil fatty acid butyl ester, and castor oil-based plasticizers such as castor oil fatty acid esters, methyl ricinoleate, ethyl ricinoleate, isopropyl ricinoleate, butyl ricinoleate, ethylene glycol monoricylate, propylene glycol monoricylate, trimethylolpropane monoricylate, sorbitan monoricylate, castor oil fatty acid polyethylene glycol ester, castor oil ethylene oxide adduct, castor oil-based polyol, castor oil-based toluol, and castor oil-based diol. These plasticizers may be used alone or in combination of two or more.

[0116] The organic filler is not particularly limited. Examples of the organic filler include fillers made of naturally derived materials such as wood-based materials (e.g., wood chips, wood flour, sawdust, etc.), rice husks, rice flour, starch, corn starch, rice straw, wheat straw, and natural rubber; organic fibers such as natural vegetable fibers, natural animal fibers, and synthetic fibers; and fillers made of synthetic resin materials such as polyester, polyacrylic, polyamide, nylon, polyethylene, polyolefin, polyvinyl alcohol, polyvinyl chloride, polyurethane, polyacetal, aramid, PBO (poly-p-phenylene benzobisoxazole), polyphenylene sulfide, acetyl cellulose, polybenzazole, polyarylate, polyvinyl acetate, and synthetic rubber.

[0117] The plant-derived natural fibers are not particularly limited. Examples of the plant-derived natural fibers include kenaf fiber, abaca fiber, bamboo fiber, jute fiber, hemp fiber, linen fiber, henequen (sisal), ramie fiber, hemp, cotton, banana fiber, coconut fiber, palm, paper mulberry, mitsumata, bagasse, etc. In addition, regenerated fibers such as pulp, cellulose fiber, and rayon processed from plant fibers are also included. Examples of the animal-derived natural fibers include wool, silk, cashmere, and mohair.

[0118] The inorganic filler is not particularly limited. Examples of the inorganic filler include silica-based inorganic fillers (e.g., quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, fillers obtained by condensing alkoxysilanes, ultrafine amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. These inorganic fillers may be surface-treated to increase dispersibility in the resin composition. In addition, these inorganic fillers may be used alone or in combination of two or more.

[0119] The antioxidant is not particularly limited. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more.

[0120] The hydrolysis inhibitor is not particularly limited. Examples of the hydrolysis inhibitor include carbodiimide compounds, epoxy compounds, isocyanate compounds, and oxazoline compounds. These hydrolysis inhibitors may be used alone or in combination of two or more.

[0121] The ultraviolet absorbing agent is not particularly limited. Examples of the ultraviolet absorbing agent include benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid compounds, cyanoacrylate compounds, and nickel complex compounds. These ultraviolet absorbing agents may be used alone or in combination of two or more.

[0122] The coloring agent such as the pigment or dye is not particularly limited. Examples of the coloring agent include inorganic coloring agents such as titanium oxide, calcium carbonate, chromium oxide, cuprous oxide, calcium silicate, iron oxide, carbon black, graphite, titanium yellow, and cobalt blue; soluble azo pigments such as lake red, lithol red, and brilliant carmine; insoluble azo pigments such as dinitrile orange and fast yellow; phthalocyanine pigments such as monochlorophthalocyanine blue, polychlorophthalocyanine blue, and polybromophthalocyanine green; condensed polycyclic pigments such as indigo blue, perylene red, isoindolinone yellow, and quinacridone red; and dyes such as oracet yellow. These coloring agents may be used alone or in combination of two or more.

[0123] The antistatic agent is not particularly limited. Examples of the antistatic agent include low molecular weight antistatic agents such as fatty acid ester compounds, aliphatic ethanolamine compounds, and aliphatic ethanolamide compounds, and polymeric antistatic agents. These antistatic agents may be used alone or in combination of two or more.

[0124] The resin composition may further contain, as additives, catalyst deactivators (hindered phenol compounds, thioether compounds, vitamin compounds, triazole compounds, polyamine compounds, hydrazine derivative compounds, phosphorus compounds, etc.), release agents (montanic acid and its salts, its esters, its half esters, stearyl alcohol, stearamide, polyethylene wax, etc.), color inhibitors (phosphites, hypophosphites, etc.), silane coupling agents (epoxy silane coupling agents, amino silane coupling agents, (meth)acrylic silane coupling agents, isocyanate silane coupling agents, etc.), flame retardants (red phosphorus, phosphate esters, brominated polystyrene, brominated polyphenylene ether ... It may also contain: aliphatic compounds such as carboxylic acid, carboxylic acid di ...

[0125] The content of each of the other components described above is not particularly limited as long as the effect of one embodiment of the present invention is exhibited, and can be appropriately set by a person skilled in the art.

[0126] <Method of producing thermoplastic resin composition> The resin composition can be produced by a known method. Specifically, the thermoplastic resin (A), the crosslinked resin particles (B), the crystal nucleating agent (C), and the lubricant and other components as optional components are melt-kneaded using an extruder, a kneader, a Banbury mixer, a kneading roll, or the like. When melt-kneading, it is preferable to mix while paying attention to the decrease in molecular weight due to thermal decomposition. The thermoplastic resin composition can also be produced by dissolving all the raw materials (components) in a soluble solvent and then removing the solvent.

[0127] When producing a thermoplastic resin composition by melt kneading, each component may be individually charged into an extruder, etc., or each component may be mixed in advance and the resulting mixture may be charged into an extruder, etc. For example, after mixing an aqueous dispersion of a thermoplastic resin with an aqueous dispersion of crosslinked resin particles (B), the resulting mixture may be dried in a dryer to obtain a mixed powder, and the mixed powder may be charged into an extruder, etc.

[0128] When melt kneading is performed using an extruder, the obtained thermoplastic resin composition may be extruded from the extruder into a strand shape and then cut, thereby processing the thermoplastic resin composition into particle shapes such as a bar shape, a cylinder shape, an elliptical cylinder shape, a sphere shape, a cube shape, a rectangular prism shape, or the like.

[0129] The resin temperature during melt kneading cannot be generally defined because it depends on the melting point and melt viscosity of the resin used, etc. The resin temperature is preferably 140°C to 250°C, more preferably 150°C to 230°C, and even more preferably 160°C to 210°C, from the viewpoint of uniformly dispersing the crosslinked resin particles (B) in the thermoplastic resin while avoiding thermal decomposition of the thermoplastic resin.

[0130] <Method of manufacturing molded body> In one embodiment of the present invention, a molded article is provided by molding the resin composition. The molding method of the thermoplastic resin composition is not particularly limited, and a commonly used molding method can be applied. Specific examples of the molding method include inflation film molding, extrusion blow molding, injection blow molding, extrusion molding, calendar molding, vacuum molding, injection molding, and the like. The molded article formed by molding the thermoplastic resin composition can also be said to be a molded article containing the thermoplastic resin composition.

[0131] By carrying out the above-mentioned molding method using the present resin composition, a molded product having excellent impact resistance, specifically, a film molded product, a sheet molded product, a blow molded product, an extrusion molded product, a vacuum molded product, or an injection molded product, can be produced with good productivity. In this specification, the term "film molded product" refers to a product conforming to JIS20108:2012, specifically, a thin film having a thickness of less than 0.25 mm. In this specification, the term "sheet molded product" refers to a product conforming to JIS20108:2012, specifically, a thin plate having a thickness of 0.25 mm or more.

[0132] Molded articles containing the present resin composition can be suitably used in fields such as agriculture, fisheries, forestry, horticulture, medicine, sanitary products, the food industry, clothing, non-clothing, packaging, automobiles, building materials, and others. EXAMPLES

[0133] The following examples are provided to more specifically illustrate one embodiment of the present invention, but the present invention is not limited to these examples.

[0134] [1] Measurement conditions 1-1. Weight average molecular weight The resin to be measured was added to chloroform, and the resulting mixture was heated in a hot water bath at 60°C for 30 minutes. The resulting mixture (chloroform solution) was filtered through a disposable PTFE filter with a 0.45 μm pore size. The filtrate was then subjected to GPC measurement under the following conditions to determine the weight average molecular weight. GPC measurement device: Shimadzu High Performance Liquid Chromatograph 20A System Column: Showa Denko KG 4A (1 column), K-806M (2 columns) Sample concentration: 1mg / ml Free solution: Chloroform solution Free liquid flow rate: 1.0ml / min Sample injection volume: 100 μL Analysis time: 30 minutes Standard sample: standard polystyrene.

[0135] 1-2.Volume average particle size The volume average particle diameter of the crosslinked resin particles (B) or the uncrosslinked resin particles was measured using the aqueous dispersion of the crosslinked resin particles (B) or the aqueous dispersion of the uncrosslinked resin particles as a sample. As a measuring device, a MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. was used. Specifically, the particle diameter and volume of each of the crosslinked resin particles (B) or the uncrosslinked resin particles in the aqueous dispersion of the crosslinked resin particles (B) or the uncrosslinked resin particles were measured using the above device, and the volume average particle diameter was calculated based on the above-mentioned formula (1), i.e., formula (2), from the results obtained by the measurement.

[0136] 1-3. Gel fraction The crosslinked resin particles (B) or the dried non-crosslinked resin particles were added to chloroform to a concentration of 0.7% by weight, and the mixture was kept at 60°C for 30 minutes to obtain a chloroform solution. After that, the mixture was left to stand at room temperature for 3 hours, and then the chloroform solution was filtered through a membrane filter with a pore size of 0.45 μm. The inside of the container and the filter were thoroughly washed with chloroform several times while filtering, to prevent loss. The gel remaining on the filter was dried, and the weight of the filter was measured, and the gel fraction was calculated using the following formula. Formula: gel fraction=(weight of filter including dry gel−weight of filter only) / weight of crosslinked resin particles (B) or uncrosslinked resin particles used in measurement×100 (%).

[0137] 1-4.Tensile impact strength A 500 μm thick molded body (sheet molded body) prepared by the method described below was aged for 7 days under conditions of 23°C and 50% RH, and then punched out into a JIS K 71603 shape to prepare a test specimen. A tensile impact test was performed on the test specimen according to the method in accordance with JIS K 7160 A method.

[0138] 1-5. Drop test of bottle-shaped molded body The bottle-shaped molded body produced by the method described below and the water to be put into the bottle-shaped molded body were placed in a thermostatic chamber adjusted to each test temperature listed in the "Temperature (℃)" column of Table 6 for 12 hours or more for curing.

[0139] The bottle-shaped molded body was then filled with the amount of water specified in the "Weight of water (g)" column in Table 6 and the lid was closed. The bottle-shaped molded body containing water was then allowed to freely drop vertically from the height specified in the "Drop height (cm)" column in Table 6 up to 10 times in succession. The condition of the bottle-shaped molded body was checked immediately after each drop, and the test was terminated when any cracks or breaks occurred. The results are shown in Table 6. If the bottle did not break after 10 consecutive drops, it was considered "good," and if it did break, the number of tries before it broke was recorded. [2] Evaluation of polyhydroxyalkanoate resins 2-1. Raw materials for crosslinked resin particles (B) 2-1-1. Uncrosslinked resin particles PHA-1: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol), weight average molecular weight Mw: 500,000 to 1.5 million PHA-2: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): (3-hydroxybutyrate) / (3-hydroxyhexanoate) = 68 / 32 (mol / mol), weight average molecular weight Mw: 500,000 to 1.5 million PHA-3: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): (3-hydroxybutyrate) / (3-hydroxyhexanoate)=75 / 25(mol / mol), weight average molecular weight Mw: 600,000~1.5 million The weight average molecular weight of each resin was measured by the method described above.

[0140] 2-1-2. Peroxide PO-1: t-butyl peroxypivalate ("Luperox (registered trademark) 11" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 76°C) PO-2: t-Butyl peroxy-2-ethylhexanoate ("Luperox (registered trademark) 26" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 95°C) PO-3: t-butylperoxy-2-ethylhexyl monocarbonate ("Perbutyl (registered trademark) E" manufactured by NOF Corporation, 1-hour half-life temperature: 119°C) PO-4: di-sec-butyl peroxydicarbonate ("Luperox (registered trademark) 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C).

[0141] 2-1-3. Polyfunctional compounds CA-1: Allyl methacrylate · CA-2: Triallyl isocyanurate.

[0142] 2-2. Manufacturing method of crosslinked resin particles (B) The types of raw materials shown in Tables 1 and 2 were used in the amounts shown in Tables 1 and 2 to produce crosslinked resin particles (B) in Production Examples 1 to 19 according to the procedures described below.

[0143] In an autoclave or glass container equipped with a stirrer, baffle, nitrogen inlet, nitrogen outlet, and thermometer, an aqueous dispersion in which uncrosslinked resin particles are dispersed in water (100 parts by weight in terms of solid content), 200 parts by weight of deionized water, a predetermined amount of peroxide, 2 parts by weight of sodium dioctyl sulfosuccinate, and a predetermined amount of polyfunctional compound were added to prepare an aqueous dispersion. The obtained aqueous dispersion was stirred at room temperature, and at the same time, the autoclave or glass container was substituted with nitrogen. Thereafter, the aqueous dispersion in the autoclave or glass container was stirred at the temperature and time of the impregnation conditions shown in Tables 1 and 2, and the peroxide and the polyfunctional compound were impregnated into the inside of the uncrosslinked resin particles.

[0144] Thereafter, the aqueous dispersion was heated to a reaction temperature under the crosslinking conditions shown in Tables 1 and 2. After the reaction temperature was reached, the reaction was continued at the reaction temperature for the reaction time and heating temperature under the crosslinking conditions shown in Tables 1 and 2, thereby obtaining an aqueous dispersion in which crosslinked resin particles (B) were dispersed in water.

[0145] After adjusting the pH of the aqueous dispersion, the dispersion was dried in an oven to obtain solidified crosslinked resin particles (B).

[0146] The volume average particle size and gel fraction of the crosslinked resin particles (B) obtained in each Example were measured by the above-mentioned methods. The results are shown in Tables 1 and 2.

[0147] The volume average particle size and gel fraction of the uncrosslinked resin particles (PHA-1) before the crosslinking reaction were measured by the above-mentioned methods. The results are shown in Table 1 as a reference example. The uncrosslinked resin particles or their aqueous dispersion were used in Comparative Examples 2 to 4 and 8.

[0148] [Table 1]

[0149] [Table 2]

[0150] 2-3. Raw materials for thermoplastic resin compositions 2-3-1. Thermoplastic resin (A) PHBH (Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)): Kaneka Corporation, Kaneka Biodegradable Polymer PHBH (registered trademark), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), repeating unit composition: (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw: 530,000, Tg 3°C 2-3-2.Resin particles Crosslinked resin particles (B): Crosslinked resin particles (B) prepared in Production Examples 1 to 19 · Uncrosslinked resin particles: PHA-1 particles 2-3-3. Nucleating agent (C) Pentaerythritol: NeuRizer P manufactured by Nippon Synthetic Chemical Industry Co., Ltd. 2-3-4. Lubricants · Behenic acid amide: BNT22H manufactured by Nippon Fine Chemicals.

[0151] 2-4. Method for producing thermoplastic resin composition (Examples 1 to 22 and Comparative Examples 1 to 4) For each Example and Comparative Example, the thermoplastic resin (A), crosslinked resin particles (B) or uncrosslinked resin particles, crystal nucleating agent (C) and lubricant shown in Tables 3 and 4 were mixed in the amounts shown in Tables 3 and 4 to obtain a mixture. The obtained mixture was melt-kneaded for 180 seconds in a twin-screw small kneader (Xplore MC5 manufactured by DSM) with the barrel temperature heated to the temperature shown in Tables 3 and 4 under the condition of a screw rotation speed of 100 rpm to obtain a melt-kneaded product (mixture). The obtained melt-kneaded product was dried in a dryer at 80 ° C. for 4 hours to sufficiently reduce the moisture content, thereby obtaining a thermoplastic resin composition of each Example and Comparative Example. Furthermore, the obtained thermoplastic resin composition was press-molded at 165 ° C. to produce a molded product (sheet molded product) having a thickness of 500 μm.

[0152] The tensile impact strength of each of the molded articles of the Examples and Comparative Examples was measured by the method described above. The results are shown in Tables 3 and 4.

[0153] (Example 23) The aqueous dispersion of thermoplastic resin (A) particles was mixed with the aqueous dispersion of crosslinked resin particles (B) prepared in Production Example 11 in a weight ratio of 70 / 30% in terms of solid content to obtain a mixture. The pH of the obtained mixture was adjusted to 3.8, and then the mixture was dried in an oven to obtain a resin mixture.

[0154] The resin mixture, the crystal nucleating agent (C) and the lubricant mixture were melt-kneaded under the same conditions as above, and a thermoplastic resin composition was obtained by the same method as above. The obtained thermoplastic resin composition was used to prepare a molded body (sheet molded body) having a thickness of 500 μm by the same method as above. The tensile impact strength of the obtained molded body was measured by the above-mentioned method. The results are shown in Table 4.

[0155] [Table 3]

[0156] [Table 4]

[0157] Tables 3 and 4 show that in Examples 1, 4, and 7 to 23, in which crosslinked resin particles (B) were blended with thermoplastic resin (A), the tensile impact strength values ​​were larger and impact resistance was improved compared to Comparative Example 1, which contained only thermoplastic resin (A).

[0158] Moreover, in Examples 1, 4, 7 to 10, 12, and 15 to 23, the tensile impact strength values ​​were larger than those of Comparative Example 3, which contained the same amount of uncrosslinked resin particles, and it is clear that the impact resistance was greatly improved by crosslinking. The same can be said from the comparison between Comparative Example 2 and Example 11, and the comparison between Comparative Example 4 and Example 13.

[0159] [3] Evaluation of bottle-shaped molded products 3-1. Method for producing bottle-shaped molded body (Examples 24, 25 and Comparative Example 5) The raw materials used were the thermoplastic resin (A), crosslinked resin particles (B), crystal nucleating agent (C) and lubricant described in the above section "2-3. Raw materials for thermoplastic resin composition." However, as the crosslinked resin particles (B), the crosslinked resin particles (B) prepared in Production Example 11 were used in the amount (parts by weight) described in Table 5.

[0160] The mixture of the thermoplastic resin (A), crosslinked resin particles (B), crystal nucleating agent (C) and lubricant was melt-kneaded in a twin-screw extruder (KZW15TWIN-45WG manufactured by Technobel Co., Ltd.) with the barrel temperature heated to 140 to 165° C. and the screw rotation speed was 80 rpm to obtain a melt-kneaded product (mixture). The obtained melt-kneaded product was dried in a dryer at 80° C. for 4 hours to sufficiently reduce the moisture content, thereby obtaining a thermoplastic resin composition of each of the examples and comparative examples.

[0161] Then, using a 30MT injection molding machine (Si-30IV manufactured by Toyo Machinery & Metals Co., Ltd.), a bottle-shaped molded body (injection molded body) with a volume of 328 ml, a thickness of 1.2 mm, an opening diameter of 66 mm, and a height of 1,010 mm was produced under conditions of a cylinder temperature of 140 to 165°C and a mold temperature of 40°C.

[0162] [Table 5]

[0163] From Table 5, it can be seen that in Comparative Example 5, in which no crosslinked resin particles (B) were blended with the thermoplastic resin (A), the bottle-shaped molded body broke on the first drop under conditions of 23°C, 100 g of water, and a drop height of 100 cm, whereas in Examples 24 and 25, in which crosslinked resin particles (B) were blended, the water weight was increased to 200 g and the bottle did not break even after 10 drops.

[0164] Furthermore, under the conditions of 2°C, 100g of water weight, and 100cm drop height, Comparative Example 5, which does not contain crosslinked resin particles (B), broke on the second drop, whereas Examples 24 and 25, which contain crosslinked resin particles (B), did not break even after 10 drops. Also, Example 25 did not break even after 10 drops when the water weight was increased to 200g under the same conditions. [Industrial Applicability]

[0165] According to one embodiment of the present invention, a novel thermoplastic resin composition capable of providing a molded article having excellent impact resistance can be provided, and therefore, one embodiment of the present invention can be suitably used in the fields of agriculture, fishery, forestry, horticulture, medicine, sanitary products, the food industry, clothing, non-clothing, packaging, automobiles, building materials, and other fields.

Claims

1. Thermoplastic resin (A) 40 parts by weight to 99 parts by weight, 1 to 60 parts by weight of crosslinked resin particles (B) containing a polyhydroxyalkanoate resin and having a gel fraction of 50% or more (wherein the total amount of the thermoplastic resin (A) and the crosslinked resin particles (B) is 100 parts by weight), and A thermoplastic resin composition comprising: 0.05 to 20.00 parts by weight of a crystal nucleating agent (C).

2. 2. The thermoplastic resin composition according to claim 1, wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin.

3. The thermoplastic resin composition according to claim 1 or 2, wherein the crosslinked resin particles (B) have a volume average particle size of 0.10 μm to 10.00 μm.

4. The thermoplastic resin composition according to claim 1 or 2, wherein the crosslinked resin particles (B) are crosslinked using a peroxide.

5. The thermoplastic resin composition according to claim 4, wherein the crosslinked resin particles (B) are crosslinked in the presence of the peroxide and the polyfunctional compound.

6. The thermoplastic resin composition according to claim 1 or 2, wherein the crosslinked resin particles (B) are not foamed.

7. The thermoplastic resin composition according to claim 1 or 2, wherein the crystal nucleating agent (C) comprises a sugar alcohol compound.

8. The thermoplastic resin composition according to claim 1 or 2, wherein the crystal nucleating agent (C) contains pentaerythritol.

9. A molded article obtained by molding the thermoplastic resin composition according to claim 1 or 2.

10. The molded article according to claim 9 , wherein the molded article is a film molded article, a sheet molded article, a blow molded article, an extrusion molded article, a vacuum molded article, or an injection molded article.

Citation Information

Patent Citations

  • Biodegradable polyester resin composition and method for producing the same

    JP2004161802A